Implementing Ki Hajar Dewantara’s Trilogy Principles in Early Childhood Islamic Education: An Implementation Study - Devi Vionitta Wibowo; Anggil Viyantini Kuswanto (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study examines the urgency of Ki Hajar Dewantara’s educational thought combined with Islamic educational values from the perspective of Abdullah Nashih Ulwan. In the context of education, the Trilogy Principles consist of three principles: Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. This study employed a descriptive qualitative research method using a case study and literature review approach. Data were obtained through observations, interviews, and documentation conducted at PAUDQU An-Nahl, Bina Qur’ani Foundation, Bogor. The findings indicate fundamental and relevant educational values between Ki Hajar Dewantara’s educational thought and Abdullah Nashih Ulwan’s Islamic educational perspective in the implementation of the Trilogy Principles in Islamic education. The implementation of the Trilogy Principles is reflected in the habituation of religious activities that embody character values and noble morals (akhlakul karimah). The methods applied in accordance with the principles of the Trilogy include habituation, supervision, advice, exemplary modeling, and mentoring to support children’s developmental aspects. The conclusion of this study is that the involvement of parents and teachers plays an essential role in instilling religious values in accordance with the Trilogy Principles and Abdullah Nashih Ulwan’s Islamic educational principles, which emphasize the roles of the home, school, and mosque.